'That might be a bit sexy for somebody your age': Older adult sexual health conversations in primary care. (21st June 2020) - Malta, Sue; Temple‐Smith, Meredith; Bickerstaffe, Adrian; Bourchier, Louise; Hocking, Jane
Abstract: Background: Many older adults are sexually active, and STIs are rising amongst this cohort. In primary care, sexual health discussions are limited as health‐care practitioners commonly assume older patients aged 60+ are not sexually active or are unwilling to discuss sex. Studies have either examined patient or clinician views, but not both. Objective: This study investigates sexual health discussions in general practice. It is unique in that it sought perspectives of different groups: older patients, health‐care professionals and key informants. Results: Qualitative interviews revealed that older patients expect clinicians to bring up sexual concerns, whereas clinicians prefer older patients to do so. A simple electronic solution to circumvent this impasse was suggested and discussed. Conclusions: Older adults would like to discuss sexual concerns with their health‐care providers. Given the rising rates of STIs in later life, sexual health discussions with older patients must become part of routine care.